2010
DOI: 10.1258/ijsa.2010.010044
|View full text |Cite
|
Sign up to set email alerts
|

Three cases of Lipschütz vulval ulceration

Abstract: A Lipschütz ulcer or 'ulcus vulvae acutum' is an acute simple ulceration of the vulva or vagina of non-venereal origin which can be associated with lymphadenopathy. Three cases are described with accompanying clinical photographs. Two cases refer to adolescents, one an infant, all without any history of sexual contact. The cases serve to illustrate a little known but potentially important differential diagnosis of vulval ulceration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The age of the patients was either in the second or third decade except in cases reported in the Archel et al 6 study (17 months), the Alés-Fernández et al 7 study (2 months), and in the Vieira-Baptista et al 8 study (79 years). None of the patients had provided their sexual history prior to the onset of genital ulcers except for the patients in the studies by Chanal et al, 9 Martín et al, 10 Brinca et al, 11 and Halvorsen et al 12 No patient history suggestive of trauma or child sexual abuse was identified.…”
Section: Resultsmentioning
confidence: 99%
“…The age of the patients was either in the second or third decade except in cases reported in the Archel et al 6 study (17 months), the Alés-Fernández et al 7 study (2 months), and in the Vieira-Baptista et al 8 study (79 years). None of the patients had provided their sexual history prior to the onset of genital ulcers except for the patients in the studies by Chanal et al, 9 Martín et al, 10 Brinca et al, 11 and Halvorsen et al 12 No patient history suggestive of trauma or child sexual abuse was identified.…”
Section: Resultsmentioning
confidence: 99%
“…Based on retrospective hospital‐based studies of women with acute genital ulcers, it is reported to vary at 4–35%, depending on the diagnostic criteria used, given that no consensus actually exists for the disease diagnosis. Most of the subsequent reports focus on the first type of ulcer described by Lipschütz displaying deep ulceration with excruciating pain of acute febrile onset, which rarely recurs . Only a few reports described the afebrile, painless and recurrent nature of the second type of ulcer which was clearly pointed out by Lipschütz .…”
Section: Brief Review Of Literaturementioning
confidence: 99%
“…Most of the subsequent reports focus on the first type of ulcer described by Lipsch€ utz displaying deep ulceration with excruciating pain of acute febrile onset, which rarely recurs. [6][7][8][9] Only a few reports described the afebrile, painless and recurrent nature of the second type of ulcer which was clearly pointed out by Lipsch€ utz. 10,11 Some retrospective studies no longer distinguished between the two kinds of ulcers mentioned by Lipsch€ utz.…”
Section: Brief Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation